Do Firms Manage Their Earnings During Initial Public Offerings? - Fuad Rakhman (The Indonesian Journal of Accounting Research, 2013)
This study investigates if IPO firms in Indonesia manage theirearnings around the time of their IPO. Using financial data from 1999to 2012, I examine the abnormal accruals of IPO firms during the threeyears prior to their IPO year and in their IPO year. I find that issuingfirms managed their earnings starting two years prior to their IPO yearand that earnings management was most profound in the IPO year. Furthertests indicate that firms used income-increasing accruals duringthe period leading to the IPO. These findings are consistent with theview that firms manage their earnings to maximize the initial offer priceand the proceeds from the IPO